ANALISIS MARGINAL REVENUE PRODUKSI TELUR AYAM LOKAL PADA USAHA AYAM PETELUR BAPAK MUSU BUNGA - Valensi Eksa; Ludia Panggalo (JURNAL ULET (Utility, Earning and Tax), 2018)
This study aims to calculate the cost of production of chicken eggs in laying chicken farms, Mr. Musu Bunga. This research was conducted on laying hens farmers owned by Mr. Musu Bunga in Irigasi (copy of Petrosea SP 2) in the new Mimika Subdistrict, district of Mimika. Site selection is done intentionally by researchers with the consideration that the farm is a farm that has a sufficient business scale. Before conducting the research, the first researcher surveyed the location by observing at a glance the laying chicken farms and conducting interviews with the farm owner and the field workers. Based on the results of research on this laying chicken farm with the full costing method, the cost of production per egg is Rp1,695